Analisis Laporan Keuangan Berdasarkan Metode Common Size Pada PT. Sentra Food Indonesia, Tbk - Debora Rayo; Helba Rundupadang; Agustinus Mantong (Universitas Kristen Indonesia Toraja, 2023)
Analysis of Financial Statements Based on the Common Size Method at PT. Indonesian Food Center, Tbk. This study aims to determine and analyze the composition of assets, debts and capital based on the general size of the financial statements of PT. Sentra Food Indonesia, Tbk in 2018-2020. This type of research is descriptive quantitative research. The data collection procedure used in this study is through documentation in the form of financial reports obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results of the study show that in terms of the common size from the balance sheet, PT Sentra Food Indonesia, Tbk. who allocated funds for assets in 2018-2019 mostly from their own capital thereby revealing a stronger financial condition of the company, while in 2019-2020 most of the funds for assets came from debt. Common size in terms of profit and loss statement, PT Sentra Food Indonesia, Tbk. In 2018-2019 there was an increase in net profit so that it can be seen that the company managed to increase sales better, while in 2019-2020 net profit decreased due to decreased sales.